2011
DOI: 10.1103/physrevc.84.021301
|View full text |Cite
|
Sign up to set email alerts
|

Spin-aligned neutron-proton pair mode in atomic nuclei

Abstract: Shell model calculations using realistic interactions reveal that the ground and low-lying yrast states of the $N=Z$ nucleus $^{92}_{46}$Pd are mainly built upon isoscalar neutron-proton pairs each carrying the maximum angular momentum J=9 allowed by the shell $0g_{9/2}$ which is dominant in this nuclear region. This structure is different from the ones found in the ground and low-lying yrast states of all other even-even nuclei studied so far. The low-lying spectrum of excited states generated by such correla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
129
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(131 citation statements)
references
References 12 publications
2
129
0
Order By: Relevance
“…With regards to the works of Refs. [12][13][14][15], this suggests the J = J max pairing is a better approximation in the upper half of a j shell rather than the lower half.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to the works of Refs. [12][13][14][15], this suggests the J = J max pairing is a better approximation in the upper half of a j shell rather than the lower half.…”
Section: Introductionmentioning
confidence: 99%
“…One obvious distinction of our work relative to that of Refs. [12][13][14][15] is that we are dealing with higher spins than the ones that they consider. In the Nature article [12], they measure J = 0, 2, 4, and 6 and also discuss J = 8, whereas the PDS that we consider occur for J = 11 + and beyond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that in this nucleus, as well as in neighboring nuclei like 96 Cd, the properties of the low-lying states can be classified by a spin-aligned np pair coupling scheme [62,63]. That is, the ground state wave functions do not consist mainly of pairs of neutrons (νν) and protons (ππ) coupled to zero angular momenta, but rather of isoscalar np pairs (νπ) coupled to the maximum angular momentum J, which in the shell 0g 9/2 is J = 9 [62,63]. A detailed shell-model analysis of the spinaligned np pair coupling was performed in Refs.…”
Section: Seniority and Np Coupling Schemesmentioning
confidence: 99%
“…A detailed shell-model analysis of the spinaligned np pair coupling was performed in Refs. [63,64] based on coefficients of fractional parentage and multistep shell model calculations.…”
Section: Seniority and Np Coupling Schemesmentioning
confidence: 99%